Persepsi Mahasiswa Program Studi Ilmu Perpustakaan Di Lingkungan Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) Tentang Prospek Kerja Lulusan - Siti Pardiani Tanjung; Abdul Karim Batubara; M Nasihudin Ali (Education : Jurnal Sosial Humaniora dan Pendidikan, 2024)
The aim of this research is to determine the extent to which library science study program students' perceptions of the knowledge of library science study program students in the PTKIN UINSU Medan and UIN Ar-Raniry Banda Aceh environment regarding graduate employment prospects as well as factors inhibiting students' understanding of graduate employment prospects and student expectations science study program towards library science study program in the future, sometimes this department is considered to only function as a book compiler or server, which makes the library science department less interesting and not widely known to many people. This type of research is qualitative descriptive research. The data analysis technique in this research uses Miles & Huberman's qualitative data analysis technique, namely data reduction, data presentation and drawing conclusions. The information obtained by researchers in data analysis is the result of observation, interviews and documentation. The number of informants from this research was 16 people, namely 9 students from UIN Ar-Raniry Banda Aceh and 6 students from UINSU Medan. The informants were determined using a purposive sampling technique who had met the criteria for library science research subjects in the final semester of study program students and had join the department association. The results of this research indicate that the knowledge of students at these two universities regarding the job prospects of IP graduates is quite good. According to students, the most promising job prospects for library science graduates in society are to become librarians and archivists. Knowledge and obstacles in understanding graduate employment prospects are influenced by internal and external factors, internal is oneself while external factors are the surrounding environment. And students' hopes for the library science study program are to become a study program in their field of learning, practice will be much better in the future and support from the campus and government for library science graduates will be given more attention.